Comparison of the carbon footprint of the dietary patterns of the inhabitants of the city of Cali and the "EAT-Lancet diet - Hurtado Bermudez, Leidy Johanna; Montoya Diaz, Juan Camilo (Bioversity International and the International Center for Tropical Agriculture, 2021)
The objective of this study is to compare, in nutritional and environmental terms, the dietary patterns of the inhabitants of Cali, Colombia, with a world reference diet based on environmental sustainability EAT-Lancet. The dietary patterns of the city were obtained through the dietary intake questionnaire of the National Survey of Nutritional Status - ENSIN in which information from 189 people between 18-64 years of age was used. By means of previous research and official sources, and considering the place of food production, the carbon footprint of the most representative foods (n=21) that are part of 8 food categories was calculated. Based on this, the daily carbon footprint of the current Cali diet and under the EAT-Lancet scenario was estimated. Under an EAT-Lancet scenario, the Cali diet would increase the grams and proportion of vegetables (247.12%) and fruit (181.95%), and would significantly reduce the intake of beef, lamb and pork (77.31%), tubers or starchy vegetables (71.80%) and eggs (70.26%). The carbon footprint of food in kg CO2eq/kg under de current diet, was estimated to be 1.27 for rice, 0.64 for corn, 0.40 for potato, 0.27 for plantain, 0.11 for citrus, 0.07 for tomato, 0.26 for onion, 0.99 for vetch, 0.69 for bean, 2.03 for milk, 8.13 for cheese, 5.00 for eggs, 2.32 for chicken, 17.63 for beef, 1.04 for palm oil, 0.47 for margarine, 3.99 for panela (unrefined sugar), and 4.60 for sugar cane. The main greenhouse gas emitting factor was manufacturing input, herd management and waste management or energy. It is estimated that the current daily Cali diet generates 1.64 kg CO2eq and under an EAT-Lancet scenario 1.51 CO2eq. In nutritional and environmental terms, the EAT-Lancet scenario diet is recommended.